Are Anthropometric Measures, Range of Motion, or Movement Control Tests Associated with Lumbopelvic Flexion during Barbell Back Squats? - Lars Berglund; Fredrik Öhberg; Edit Strömbäck; Daniel Papacosta (North American Sports Medicine Institute, 2024)
# Background Resistance training with the barbell back squat (BBS) exercise is practiced in sports, recreation, and rehabilitation. Although extensively debated, it is commonly believed and recommended that maintaining a neutral lumbopelvic alignment during BBS is an important technical aspect that might reduce the risk of injury. There is limited knowledge of how objectively measurable factors affect the extent to which the lumbopelvic region moves into flexion during a BBS. # Purpose The aim of the study was to investigate the association among anthropometric measurements, range of motion in the hips and ankle joints, lumbopelvic movement control tests, and flexion of the lumbopelvic region during execution of the BBS. # Study design Observational, cross sectional. # Methods Eighteen experienced powerlifters and Olympic weightlifters were included and measurements of lumbopelvic movements were collected with inertial measurement units during BBS performed at 70 % of 1RM. Examination of anthropometric properties, range of motion in the hip and ankle joints, and lumbopelvic movement control tests were collected as independent variables. Linear regression analysis was used to investigate which independent variables were associated with lumbopelvic flexion during a BBS. # Results The linear regression showed that a higher range of motion in ankle dorsiflexion could statistically significantly explain an increased amplitude of lumbopelvic flexion during the BBS. Anthropometrics, range of motion of the hips, and performance in lumbopelvic movement control tests did not show any statistically significant associations. # Conclusions The results suggest that strength and conditioning professionals and clinicians who instruct and assess lifting technique in the BBS and/or use the BBS to assess performance or as an intervention should recognize that a higher range of motion in the ankle joints might affect lumbopelvic flexion during the BBS. In practice, the value of an individual assessment of lifting technique focusing on the goal of the movement should be emphasized. # Level of Evidence 3